2016
DOI: 10.1103/physreve.93.013203
|View full text |Cite
|
Sign up to set email alerts
|

Fast magnetic-field annihilation in the relativistic collisionless regime driven by two ultrashort high-intensity laser pulses

Abstract: The magnetic quadrupole structure formation during the interaction of two ultrashort high power laser pulses with a collisionless plasma is demonstrated with 2.5-dimensional particle-in-cell simulations. The subsequent expansion of the quadrupole is accompanied by magnetic-field annihilation in the ultrarelativistic regime, when the magnetic field cannot be sustained by the plasma current. This results in a dominant contribution of the displacement current exciting a strong large scale electric field. This fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Analysing this realm of processes, Syrovatskii [75] first proposed the dynamic dissipation of the magnetic field. Theoretical and numerical works demonstrated the intensive charged particles acceleration in the MR current sheet driven by inductive electric field and proved the important role of displacement current in such an ultra-relativistic process [76,77] . Recent kinetic simulation in a 3D geometry presented the electron ejection from the non-adiabatic region in MR, the formation and evolution of the current sheet with the growth of tearing-like mode instability [78] .…”
Section: Introductionmentioning
confidence: 92%
“…Analysing this realm of processes, Syrovatskii [75] first proposed the dynamic dissipation of the magnetic field. Theoretical and numerical works demonstrated the intensive charged particles acceleration in the MR current sheet driven by inductive electric field and proved the important role of displacement current in such an ultra-relativistic process [76,77] . Recent kinetic simulation in a 3D geometry presented the electron ejection from the non-adiabatic region in MR, the formation and evolution of the current sheet with the growth of tearing-like mode instability [78] .…”
Section: Introductionmentioning
confidence: 92%
“…Although the number of the positrons and the creation efficiency is not very high, the positron beam obtained in our mechanism is ultra-short and has ultra-relativistic energy. Several mechanisms have been proposed recently for positron creation and acceleration [30][31][32][33][34]. The positron bunches created in this paper can be used as an ideal external injection source for further acceleration.…”
Section: Positron Bunch Productionmentioning
confidence: 98%
“…In our recent research using 2D Particle-in-cell (PIC) simulations, we have found that fast relativistic magnetic annihilation is achieved with two parallel ultra-short petawatt laser pulses co-propagating in an underdense plasma (see Fig. 22 (a)) [44,45]. The two magnetic dipoles generated by the laser pulses annihilate in the current sheet formed at the central axis.…”
Section: Laboratory Astrophysicsmentioning
confidence: 99%